Determine the Effects of Alkaline Excipients on Preparing Alpha-lipoic Tablets - Bao, Tran Ngoc; Chien, Nguyen Ngoc; Viet Linh, Mai; Duc Trung, Nguyen; Van Hai, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 3DO - 10.25073/2588-1132/vnumps.4719, 2025)
The development of alpha-lipoic acid (ALA) tablets has emphasized several issues, including instability to light and temperature, and poor dissolution rate of tablets. Due to free carboxylic acid groups in the ALA chemical structure, the objective of this study was to investigate the role of alkaline excipients in tablet composition on the dissolution and stability of the active ingredient through the interaction mechanism with this functional group. Alkaline excipients were added to the binders or combined with the filler excipients in the wet granulation process. The DSC and IR were used to assess the interactions between ALA and alkaline excipients. Effects of different molar ratios of ALA: alkaline excipients and the filler excipients (Fluorite, FLR, calcium silicate) on the solubility of tablets were also investigated. The obtained results showed that adding alkaline excipients enhanced the stability of ALA in temperature-stability experiments (100 o C, 1h). Combining alkaline excipients in the formula also increased dissolution rates, in which lysine (0.3%) and NaEDTA (2.0%) were the two best alkaline excipients. The final formulation, including ALA (66.67%), MCC (25%), FLR (6.33%), and NaEDTA (2.0%), was proposed. The dissolution complied with the US Pharmacopoeia criteria (over 90% ALA dissolved in 60 minutes).